In the Year of the Rat. From infection to poisoning in David Peace's Occupied City (Altre Modernità, 2014)
Susan Sontag’s probably most influencing work – her reflection on the metaphoricaura enveloping certain diseases – may be of some use in introducing my approach toDavid Peace’s narrative, with particular reference to the so called Tokyo Trilogy